Co-implementation of conservation tillage and herbicides reduces weed and nematode infestation and enhances the productivity of direct-seeded rice in North-western Indo-Gangetic Plains - Raj, Rishi; Das, T. K.; Pankaj,; Banerjee, Tirthankar; Ghosh, A.; Bhattacharyya, Ranjan; Chakraborty, Debashis; Prasad, Shiv; Babu, Subhash; Kumar, Vikash; Sen, Suman; Ghosh, Sonaka (Frontiers in Sustainable Food Systems, 2022)
Direct-seeded rice (DSR) can be a resource-efficient alternative to puddled transplanted rice (PTR), but weeds and nematodes pose severe challenges. Conservation agriculture (CA)-based DSR may inhibit/influence weeds/nematodes, which can be further intensified by adopting better weed control. Hence, this experiment was undertaken. Five CA-based DSR practices involving zero tillage, residue retention, brown manuring, and superimposed with four weed control/herbicide options were compared with PTR in a split-plot design replicated three times. All DSRs encountered more weeds and plant parasitic nematodes (PPNs) than PTR. Root-knot nematodes (RKN) infested five among 14 weeds present in rice and was first time found in Dinebra retroflexa. A CA-based zero till (ZT)DSR+ mungbean residue – ZT wheat + rice residue – ZT mungbean+wheat residue system reduced weeds significantly. It reduced RKN galls in Echinochloa colona, Echinochloa crusgalli, and rice plants by 72, 58, and 56%, respectively. In soil too, RKN and other PPNs, namely, Tylenchorhynchus brevilineatus and Pratylenchus thornei were reduced by 39%, 32%, and 26%, respectively, which gave a 6.3–22.7% higher yield in this CA practice than other DSRs. Pyrazosulfuron-ethyl, cyhalofop-butyl, and bispyribac-Na applied sequentially reduced weeds and PPNs, increased rice yield by 176.1%, and were at below detectable levels in soil, rice grains, and straw, and were safe for rotational crops. The above ZT-based triple cropping with residue supplemented with herbicides through better weed and nematode control would be an alternative to PTR in the North-wester Indo-Gangetic Plains of India and in similar agroecologies of the tropics/sub-tropics. This study would help farmers and policymakers to design integrated weed and nematode management modules using tillage, crop residue, and herbicides/pesticides for higher DSR yield and income.